Socialization Mediators of the Relation between Socioeconomic Status and Child Conduct Problems - Dodge, Kenneth A.; Pettit, Gregory S.; Bates, John E. (Child development, 1994)
The goal was to examine processes in socialization that might account for an observed relation between early socioeconomic status and later child behavior problems. A representative sample of 585 children (n=51 from the lowest socioeconomic class) was followed from preschool to grade 3. Socioeconomic status assessed in preschool significantly predicted teacher-rated externalizing problems and peer-rated aggressive behavior in kindergarten and grades 1, 2, and 3. Socioeconomic status was significantly negatively correlated with 8 factors in the child's socialization and social context, including harsh discipline, lack of maternal warmth, exposure to aggressive adult models, maternal aggressive values, family life stressors, mother's lack of social support, peer group instability, and lack of cognitive stimulation. These factors, in turn, significantly predicted teacher-rated externalizing problems and peer-nominated aggression and accounted for over half of the total effect of socioeconomic status on these outcomes. These findings suggest that part of the effect of socioeconomic status on children's aggressive development may be mediated by status-related socializing experiences.